2001
DOI: 10.1053/jlts.2001.22324
|View full text |Cite
|
Sign up to set email alerts
|

Fitness testing of pediatric liver transplant recipients

Abstract: Liver transplantation is accepted as the standard management for end-stage liver disease in children. Pediatric heart and heart-lung transplant recipients have shown significantly diminished exercise capacities compared with age-matched, able-bodied, control subjects. The primary aim of this study is to compare the fitness levels of a group of pediatric liver transplant (LT) recipients (LT group, 20 boys, 9 girls; age, 8.9 ؎ 4.8 years; 56 ؎ 35 months posttransplantation) with a group of able-bodied control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…The FITNESSGRAM has been used to assess the physical fitness of pediatric liver TX recipients by Unnithan et al [27] and Krasnoff et al [37]. Similar to our results, there was only one subject who achieved the HFZ for the PACER test of cardiorespiratory fitness in the Krasnoff study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The FITNESSGRAM has been used to assess the physical fitness of pediatric liver TX recipients by Unnithan et al [27] and Krasnoff et al [37]. Similar to our results, there was only one subject who achieved the HFZ for the PACER test of cardiorespiratory fitness in the Krasnoff study.…”
Section: Discussionsupporting
confidence: 88%
“…This testing has not been widely used in clinical pediatric populations. Unnithan et al [27] reported FITNESSGRAM data on 29 pediatric liver TX recipients (12 girls, 22 boys). None of the children achieved criterion-referenced healthy fitness standards for cardiorespiratory fitness, and only 35% of the sample attained the muscle strength standard.…”
Section: Introductionmentioning
confidence: 99%
“…These included aerobic capacity (progressive aerobic cardiovascular endurance run, PAC-ER); muscle endurance (curlup), and flexibility (backsaver sit and reach). The FITNESSGRAM has been found useful in clinical research in children with solid organ transplants [5,6,26]. Our study applied a similar protocol as that used by two earlier studies [5,6] in order to determine whether children with kidney transplants achieved the HFZ.…”
Section: Field Testingmentioning
confidence: 99%
“…Excessive weight gain post-transplant occurs in a large number of pediatric solid organ recipients; however, the natural history of obesity in this population has not been addressed (95). In a study by McDiarmid et al, only 10% of pediatric liver recipients with hyperlipidemia engaged in routine exercise (McDiarmid, UCLA, personal communication 2000).…”
Section: Obesity and Sedentary Lifestylementioning
confidence: 99%